Mortality and Cardiovascular Events in Patients With Chronic Kidney Disease and Sleep Apnea Syndrome - Watanabe, Yu; Tanaka, Akihito; Furuhashi, Kazuhiro; Saito, Shoji; Maruyama, Shoichi (Frontiers in Medicine, 2022)
Background: The incidence of sleep apnea syndrome (SAS) is reported to be markedly high in patients with chronic kidney disease (CKD). Therefore, it is extremely important to know whether SAS affects prognosis in patients with CKD. Further, it is imperative to understand the prognostic impact of home continuous positive airway pressure (CPAP) therapy, which is one of the most common treatments for SAS. Methods: We used a clinical database to identify patients with CKD using diagnosis codes. We included patients with CKD aged 20 years or more, not on renal replacement therapy, with a known change in renal function for at least one year. The propensity score was used to compare event rates for patients with SAS and those without SAS. In addition, the prognostic impact of CPAP therapy was investigated. The primary outcome is a composite of death, initiation of renal replacement therapy, hospitalization for heart failure, ischemic heart disease, and cerebrovascular disease. Results: From the database, 31,294 patients with CKD without SAS and 1,026 with SAS were found to be eligible. Of these, 419 (41%) patients with SAS and 10,713 (34%) patients without SAS (P<0.01) reached the primary outcome. After adjustment with the propensity score, the SAS group was found to have a similarly poor prognosis (P<0.01): the hazard ratio for the primary outcome was 1.26 (95% CI, 1.08-1.45, P<0.01) in the group with SAS compared with the group without SAS. Conversely, in patients with SAS and using CPAP, the hazard ratio was lower and did not differ significantly (HR 0.96, 95% CI: 0.76-1.22, P=0.76). Conclusion: In patients with CKD and SAS, the risk of death and cardiovascular disease is high. In addition, patients treated with CPAP may have improved life expectancy.